LIFE EXPERIENCE OF THE FOUR OLD MEN RITUAL SPEECH OF TRADITIONAL BRIDE AND GROOM CEREMONY - Agostinho dos Santos Gonçalves; Jose Antonio Sarmento; Maria Magno Guterres (Jurusan Sastra Indonesia, 2020)
The purposes of this study are to know the meaning and function of the ritual speech of traditional bride and groom ceremony, to identify the value of culture, education, religion moral and justice of ritual speech, to analyze and describe the ritual speech within positive and negative impacts of bride and groom. This study Phenomenological study through in-depth interview with the four informants' life experience, in Seloi, Aileu. The Ritual Speech is one of the local wisdom. The function of the ritual speech is celebrated for living together between the bride and groom to become a new family in peace and love. The ritual speech has a value of culture, education, religion moral and justice. The result shows two impacts: positive if it brings family wellbeing. The negative impact if ritual speech is not conducted it brings bad luck for the family. Therefore, the ritual speech needs to preserve and to develop as the traditional law. Ritual Speech of traditional bride and groom ceremony needs to consider as subject local content of the school curriculum.